Association between incretin-based drugs and risk of cholangiocarcinoma among patients with type 2 diabetes: A large population-based matched cohort study - Arunkumar Krishnan; Carolin V. Schneider; Hendrik-Tobias Arkenau; Ezequiel Matias Mauro; Alejandro Forner; W. Scott Butsch; Declan Walsh; Saleh A. Alqahtani (Journal of Clinical & Translational Endocrinology)
Aim: To examine the association between the use of incretin-based drugs [glucagon-like peptide-1 receptor agonists (GLP-1RAs), dipeptidyl peptidase-4 inhibitors (DPP-4Is)] and the risk of cholangiocarcinoma (CCA) in the United States. Methods: This large population-based, retrospective cohort study using the TriNetX datasets included adult patients with type 2 diabetes mellitus (T2DM) who were new users of GLP-1RAs, DPP-4Is, or other second- or third-line antidiabetic drugs between 2010 and 2021. The primary outcome was the incidence of CCA. Results: A total of 3,816,071 patients were included (mean age, 61.4 years, female, 49.3 %). A 51 % and 23 % risk reduction in CCA after 1 year of exposure to GLP-1RAs (hazard ratio 0.49; 95 % CI 0.40–0.60) and DPP4Is (0.77, 95 % CI 0.67–0.90), respectively compared to new second-or third-line users. Results were consistent at 3, 5, and 7 years of follow-up (0.66, 0.71, and 0.72 for GLP-1RAs and 0.84, 0.87, and 0.85 for DPP-4Is, respectively). Compared to new metformin users, GLP-1RA users were associated with a 42 % lower risk of developing CCA, whereas DPP-4I group was not associated with an increased risk. Conclusions: GLP-1RAs and DPP-4Is were not associated with a significantly increased risk of CCA. GLP-1RAs even showed a reduced risk of CCA development. They can be considered as safe and effective treatment options for patients with T2DM at risk of CCA.